Konseling kelompok dengan teknik cognitive behavior therapy untuk meningkatkan kontrol diri dalam penggunaan smartphone - Henny Rofiah; Devi Ratnasari; Christine Masada Hirashita Tobing (Universitas Indraprasta PGRI, 2023)
the aim of the research was to find out about group counseling services, cognitive behavior therapy techniques in increasing smartphone self-control in students of Madrasah Tsanawiyah Arridho Depok. The research used is quantitative research with experiments using one group pretest and posttest design. The population in this study were 141 students in class VIII with a purposive sampling technique. The instrument used was a questionnaire adapted from a thesis that was relevant to the research. Data analysis technique was performed by Wilcoxon signed rank test. The results of the study generally concluded that group counseling cognitive behavior therapy techniques was effective in increasing students' self-control in using smartphones. The results of this study are useful for schools in designing group counseling programs to be more effective in helping develop potential and alleviating students' problems.